From struggle to success: how to use aesthetics to improve business relationships - Ladkin, Donna (Henry Stewart Talks, 2019)
This case study tells the story of a professional who found that relations with a particular client were becoming strained and adversarial. By working on the aesthetics of their interactions, she managed to transform the underlying relationship and create a more positive working environment.
Archived at 2024/02/11